ANALISIS PERKEMBANGAN KEMAMPUAN MEMBACA MENGGUNAKAN MEDIA BUSY BOOK PADA SISWA DOWN SYNDROME SEKOLAH DASAR - Melati Aina Sukmaning Prasetyo; Galuh Kartika Dewi; Tri Achmad Budi Susilo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is rooted in the importance of inclusive education and the limitations experienced by students with Down Syndrome in language skills, particularly in reading. The Busy Book was chosen as an innovative solution to enhance students’ motivation, concentration, and reading ability through an engaging and interactive learning approach. The objective of this study is to analyze the development of reading skills in students with Down Syndrome at the elementary level using the Busy Book as a learning medium. This study employs a descriptive quantitative method, with data collected through reading tests and student response questionnaires conducted at SDI Al-Chusnaini, Sukodono. The research subjects consist of two students with Down Syndrome. The results indicate that the use of the Busy Book had a positive effect on students’ reading skills. The average increase in the reading test score of student 1 was 46.66%, while student 2 showed an improvement of 26.67%. Additionally, student 1’s response to the media showed a higher average score of 63.89% compared to student 2’s score of 52.78%. Student 1 demonstrated greater interest, focus, and independence, while student 2 tended to experience confusion and lacked focus. Thus, the Busy Book has proven to be effective in enhancing the reading skills of students with Down Syndrome at the elementary school level, with a recommendation to adjust the media according to the preferences and needs of each student.